Respuestas

2012-08-23T02:20:47+02:00
 

 

- 1 3 1) lim ------- = -- x->2 3x - 4 2

 

- 1 3 2) lim -------- = -- = +inf x->2 x - 2 0 -2x

 

+ 5x - 2 0 3) lim -------------- = -- INDETERMINADO x->2 3x

 

- 2x - 8 0

4) 3x

3

+ 2x

2

- 5 3x

3

3 lim -------------- = lim ----- = -- x->+inf 2x

3

- 8x

2

x->+inf 2x

3

2

5)(IND. inf - inf) 3 ____________ 3 ___________ | lim 2 + \|x

3

- 3x

2

+ 1 - \|x

3

- 4x + 1 = x->-inf x

3

- 3x

2

+ 1 - x

3

+ 4x - 1 2 + lim ----------------------------------------------------- = x->-inf 3 __________ 3 _________ 3 ___________________ \|(x

3

-3x

2

+1)

2

+ \|(x

3

-4x+1)

2

+ \|(|x

3

-3x

2

+1)(x

3

-4x+1) -3x

2

2 + lim ---- = 2 - 1 = 1 x->-inf 3x

2